2011
DOI: 10.1186/1471-244x-11-93
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of patients with and without substance use disorders in Community Mental Health Centres

Abstract: BackgroundEpidemiological studies have consistently established high comorbidity between psychiatric disorders and substance use disorders (SUD). This comorbidity is even more prominent when psychiatric populations are studied. Previous studies have focused on inpatient populations dominated by psychotic disorders, whereas this paper presents findings on patients in Community Mental Health Centres (CMHCs) where affective and anxiety disorders are most prominent. The purpose of this study is to compare patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…that substance use is common among patients diagnosed with psychiatric disorders. The results of this study need to be interpreted cautiously, as previous studies found that the lifelong substance use rate among patients with psychotic disorders range from 11.0 to 34% . The results, in general, provide new insight into the co‐occurring substance use and mental disorders.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…that substance use is common among patients diagnosed with psychiatric disorders. The results of this study need to be interpreted cautiously, as previous studies found that the lifelong substance use rate among patients with psychotic disorders range from 11.0 to 34% . The results, in general, provide new insight into the co‐occurring substance use and mental disorders.…”
Section: Discussionmentioning
confidence: 65%
“…The results of this study need to be interpreted cautiously, as previous studies found that the lifelong substance use rate among patients with psychotic disorders range from 11.0 to 34%. 5 The results, in general, provide new insight into the co-occurring substance use and mental disorders. Although the study did not assess the comorbidity of mental and substance abuse, and rather emphasized the association and prevalence of substance use among patients diagnosed with mental disorders, the study raises the need to pay more attention to screen for substance use and abuse among psychiatric patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is clinically important as this co-morbidity has a negative impact on the treatment of both conditions (3). While many different epidemiological factors contribute to this phenomenon, inconsistent results have been observed in different studies (8). As a result, the findings could not be generalized to other societies and even to a certain disease.…”
Section: Introductionmentioning
confidence: 90%